ANALYSIS OF THE EROSIVE POTENTIAL OF THE CACAU PIRÊRA HYDROGRAPHIC BASIN, IRANDUBA, AMAZONAS STATE, BRAZIL - Vidal, Bruno Sarkis; Silva Neto, João Cândido André da (Geosaberes, 2020)
It is observed in the metropolitan region of Manaus after the implementation of the Phelippe Daou Bridge, which connects Manaus with Iranduba, a growing process of changes in land use and plant cover. Thus, the objective was to analyze the potential for laminar erosion in the Igarapé do Cacau Pirêra watershed. That said, were processed satellite images, vectorial, matrix and numerical terrain data were processed using Geographic Information System (GIS), enabling the implementation of spatial analysis, supported by the decision support. It was observed that 9.62% of the basin area has land use compatible with the susceptibility to laminar erosion, the medium potential is the most expressive class of the basin, with 75, 99%; and the upper and very upper classes are present in 14.39% of the total basin area, presenting incompatibility of land use and vegetation cover.